Perceptions of Childcare and Parenting Support among Working Parents - Aghaziarati, Ali; Faramarzi, Salar (Journal of Psychosociological Research in Family and Culture, 2024)
Objective: The objective of this study was to explore the perceptions of childcare and parenting support among working parents. Method: This qualitative study employed semi-structured interviews with 20 working parents from diverse professional backgrounds. Participants were selected using purposive sampling to ensure a balanced representation of genders and a variety of family structures. The interviews were conducted either in person or via video conferencing, lasting between 45 and 60 minutes. Data were analyzed thematically using NVivo software, following a systematic coding process to identify key themes and patterns. The final sample size was determined by theoretical saturation. Results: Three main themes emerged from the analysis: experiences with current childcare arrangements, challenges in balancing work and parenting responsibilities, and access to and satisfaction with parenting support resources. Parents reported limited availability and high costs of childcare, concerns about quality, and a need for flexible services. Challenges included time management, employer support, stress, and the impact on career advancement. Informal support networks, such as family and friends, played a crucial role, while formal support services were beneficial but often underutilized due to lack of awareness. Conclusion: The study highlights the complex challenges faced by working parents in managing childcare and parenting responsibilities. Findings underscore the need for more flexible, affordable, and high-quality childcare services, along with stronger support systems within the workplace and community. By addressing these needs, policymakers, employers, and childcare providers can improve work-family balance and overall well-being for working parents. The insights gained can inform the development of more effective policies and practices, ultimately benefiting parents, children, and society.